The Influence of Social Media Communication and Service Quality on Patient Loyalty with Patient Trust as a Mediating Variable in Eye Health Services in Surabaya - Eko Riswanto; Samsul Arifin; Siti Mujanah; I Made Suparta (International Journal of Economics (IJEC), 2026)
The digital transformation of healthcare services has shifted the determinants of patient loyalty from solely clinical outcomes to relational dimensions and digital communication. Despite the growing use of social media in healthcare, studies that simultaneously integrate social media communication and service quality on patient loyalty, mediated by trust, particularly in eye healthcare services, are still limited. To analyze the direct and indirect effects of social media communication and service quality on patient loyalty through the mediation of patient trust in eye healthcare services in Surabaya. A quantitative cross-sectional survey was conducted with 100 randomly selected eye clinic patients. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Measurement and structural model evaluations were conducted, along with mediation testing using bootstrapping. Social media communication and service quality significantly influenced patient trust. The direct effect on patient loyalty was also significant for social media communication, service quality , and patient trust. Patient trust partially mediated the relationship between social media communication and loyalty (indirect effect) and the relationship between service quality and loyalty (indirect effect). The model explained 52.1% of the variance in patient trust and 61.2% of the variance in patient loyalty, with satisfactory predictive relevance. Social media communication serves not only as an informational tool but also as a relational channel for building trust in ophthalmology services. Service quality remains the primary foundation of trust and loyalty. Managers need to integrate digital communication strategies with service excellence, leveraging patient trust as a key mechanism for maintaining long-term loyalty